Resources evaluation of Antarctic krill Euphausia superba Dana using areal trawling and hydro-acoustic data - Kovalchuk, L. A. (Ukrainian Antarctic Journal, 2004)
Quantitative method for describing krill mass congestions based on perennial observations using trawling and hydroacoustic data is proposed. Reliable evaluation of krill resources is provided with probability methods and spatial analyses requiring knowledge of statistical distribution rules applicable for natural habitat and equal probability concentrations. Spatial analyses of krill population densities have shown mixed rules of statistical distribution over its natural habitat. Data analyses procedures applied for trawling and hydro-acoustic sampling have to in compliance with the rules of statistical distribution and principles of metrology. Division of natural habitat of the Antarctic krill into regions is based on a principle of equal probability applied for congestions instead of the principle of equal proportions. Metrological features of evaluating population densities of krill are revealed. Standard measures for the population densities of krill in natural habitat are not available, thus it is principally impossible to structure systems and random errors in evaluating process, to define their impact on final evaluation of the resource. Special metrological principles are required and proposed for the correct evaluations based on reproducibility of statistic distribution parameters for krill and minimizing miscalculations in evaluations of congestions. Evaluations regime applied for the population density of krill should be defined by reliability and admissible error of estimated resource. Traditional concepts of observation system concerning the resources of krill should be further developed with applications of rules and parameters dealing with statistical distributions of population density, information about sources of errors, tools and methods of evaluation, standard techniques of minimizing errors in evaluations taking into account biological features of krill development. Methodical standards and uniform evaluation criteria for parameter evaluations of statistical distributions should be proposed to the Countries participating in the Antarctic Treaty as proceedings regarding minimal errors in the evaluation procedure. Reliable evaluation of krill resources requires advanced technical tools and observation systems. Population density values for krill should be calculated using Aitchison delta distribution. Primary statements regarding the krill in strategic planning for fisheries should include relevant biologically valid evaluations of population numbers for krill with the maintained reliability requirements and reasonable errors in evaluating the density of populations.